Management of abiotic stress in barley (Hordeum vulgare L.) - Rani, Sonia; Chaudhary, Ankur; Rani, Kanta (Journal of Cereal Research, 2018)
Globally, abiotic stresses are the major limiting factor in achieving optimum production and productivity of various crops. These stresses cause about 50% reduction in yields of various crops. Although, barley (Hordeum vulgare L.) is a comparatively abiotic stress tolerant crop still abiotic stresses (drought, salinity, sodicity, acidity, water logging, heat, nutrient toxicities/ deficiencies etc.) affect the barley production and productivity. The duration of the stress and the plant's growthÂ stage at which stress occurs affects the yield. For the sustainable barley production, there is need that various abiotic stresses be effectively addressed through the adoption of management practices like tillage and planting options, residue management, sowing time, stress tolerant cultivars, irrigation scheduling, and integrated nutrient management. Barley potential to cope up against abiotic stress can be further accelerated by synchronizing breeding and agronomic, climatic driven and location-specific researches.Â Doi. org/10.25174/2249-4065/2018-85229